Detailed characterization of lectin genes in common bean using bioinformatic tools - Aras, Sümer (Ankara Üniversitesi Fen Fakültesi, 2022)
Because of differences in molecular structure, biochemical properties, and carbohydrate binding specificity, lectins are considered a complex and heterogeneous group of proteins found in all organisms. Plant lectins are important proteins in terms of their benefits in cancer treatments, biomedical applications, and many medical uses due to their numerous biological roles such as intercellular interactions, defense mechanisms formation, immunomodulation, and anticarcinogenic activity. Despite the discovery of significant amounts of lectin proteins in different plant species, many questions about their potential biological role remain unanswered in P. vulgaris L. In this study, using bioinformatics tools, 52 Pvul-LEC genes were identified in the P. vulgaris genome and these genes were clustered into three subgroups based on phylogenetic analysis. The majority of Pvul-LEC proteins in the same subfamily of phylogenetic tree shared similar motifs and gene structures. Eight pairs of segmental duplications were discovered based on genome wide duplication analysis. Pvul-LEC proteins' three-dimensional structure and functions were also predicted. Simultaneously, gene expression levels of Pvul-LEC genes against drought and salt stress in leaf tissues were evaluated based on publicly available RNAseq data. As a result, it is anticipated that the data obtained in the current study will be beneficial to literature and following studies related to lectin genes.
Keywords: Lectin; RNAseq; common bean